THE READINESS OF FUTURE MARINE ENGINEERS TO PROFESSIONAL ACTIVITY IN ARCTIC REGION - Tatyana I. Radionovskaya (Высшее образование в России)
The article explores the satisfaction level of the learning process among the students and cadets of Maritime Academy of Murmansk State Technical University. We have conducted an analysis of survey results of future engineers on the professional compliance to marine-related activities and the readiness to work in Arctic conditions and have made a correlation analysis of the received data. A high level of of future engineers’ readiness to work in the Arctic is justified by high motivation towards learning and specialized training. We correlate the features of marine engineers’ training with the requirements of national and international standards, codes and conventions. The young northerners receiving engineering education are ready to apply their knowledge to meet the challenges of the development of the Arctic region.